2020
DOI: 10.1186/s13020-020-00344-8
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analyses revealed the ultraviolet B irradiation and phytohormone gibberellins coordinately promoted the accumulation of artemisinin in Artemisia annua L.

Abstract: Background: Artemisinin-based combination therapy has become the preferred approach for treating malaria and has successfully reduced malaria-related mortality. Currently, the main source of artemisinin is Artemisia annua L., and thus, it is of strategic importance to enhance artemisinin contents in A. annua plants. Phytohormones and illumination are known to be important external environmental factor that can have notable effects on the production of secondary metabolite. The activities of different hormones … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 70 publications
(87 reference statements)
0
9
0
1
Order By: Relevance
“…GAs also have a positive regulatory effect on artemisinin content and yield. Metabolome and transcriptome analysis by Ma et al (2020) revealed that GA and UV-B irradiation coordinately promoted artemisinin accumulation in A. annua by up-regulating key biosynthetic genes like ADS and CYP71AV1. Co-overexpression analysis suggested that certain selected NAC and MYB transcription factors regulated the expression of these genes to enhance artemisinin production.…”
Section: Use Of Phytohormonesmentioning
confidence: 99%
“…GAs also have a positive regulatory effect on artemisinin content and yield. Metabolome and transcriptome analysis by Ma et al (2020) revealed that GA and UV-B irradiation coordinately promoted artemisinin accumulation in A. annua by up-regulating key biosynthetic genes like ADS and CYP71AV1. Co-overexpression analysis suggested that certain selected NAC and MYB transcription factors regulated the expression of these genes to enhance artemisinin production.…”
Section: Use Of Phytohormonesmentioning
confidence: 99%
“…And DAVIDJ.BURRITT and SUSAN MACKENZIE's study on a shade-loving plant named Begonia×erythrophylla also showed the same result, that the content of ChlA and ChlB decreased in plant leaves when the plant was placed under conditions of full light [40]. It has been found that the activities of different hormones can be in uenced to varying degrees by light [41]. The results indicate that strong illumination is a major stress disorder faced by L. rotata in the F. rubra+L.…”
Section: Morphological Structure Of Leafmentioning
confidence: 85%
“…Our data also agree with previous transcriptome studies showing that a large number of plant genes were differentially regulated by UV-C radiation, as for P. cuspidatum in which nearly 25% of the expressed genes were affected [ 35 ]. Moreover, the number of genes identified in different plants as DEGs upon UV exposure was notably higher compared to those modulated by other stimuli, such as gibberellins treatment [ 74 ], heavy metals and ionizing radiation [ 75 ], low temperature [ 68 ], and jasmonate and salicylate treatments and herbivore infestation [ 76 ].…”
Section: Discussionmentioning
confidence: 99%